Factors influencing exclusive breast feeding among women attending maternal and child health clinic at Kyanamira health centre 111, Kabale district - Topher, Byamukama; Patience, Akandind (International Journal of Community Medicine and Public Health, 2023)
Background: There is an increasing trend of mothers failing to exclusively breastfeed their babies and this has led to an increasing number of malnourished babies worldwide. This study was aimed at determining the factors that influence exclusive breastfeeding in Kyanamira HC III. Methods: A systematic random sampling technique was used to get all the 175 study participants. Results: 64% of the study participants were aged between 20 and 30 years, and 86.6% of them were peasants. The study found out a strong negative statistical association between community perception and exclusive breast feeding (p=-0.141, r=0.182), and majority of the mothers (62.6% do not support Exclusive breast feeding. There was no positive significant value related to exclusive breastfeeding in our study. Conclusions: Factors that are negatively influencing exclusive breast feeding in Kyanamira HC III are social, cultural and maternal physiological factors